1990
DOI: 10.1002/bjs.1800770612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coloscreen self-test® and Haemoccult® faecal occult blood tests in the detection of colorectal cancer in symptomatic patients

Abstract: The usefulness of faecal occult blood tests is limited by their acceptability to patients. Standard tests require the collection of a stool sample which may inhibit compliance. Self-read tests which avoid this step have therefore been devised. Coloscreen Self-Test (CST) and Haemoccult, which may be regarded as the standard slide test, were offered to 450 consecutive patients attending surgical outpatient clinics with symptoms suggestive of lower gastrointestinal disease. Both tests were successfully completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…This is within the range of 50-86% quoted in the NHSME CRC Needs Assessment Review (2), and corresponds most closely with the levels of 54% and 58% reported in 1990 and 1992 for non-rehydrated guaiac tests in preliminary results from the Nottingham trial (21,22). Rehydration of guaiac FOBT slides only yields greater sensitivity at the price of lower specificity, ie higher false-positivity rates.…”
Section: Sensitivity Of Fortsupporting
confidence: 82%
“…This is within the range of 50-86% quoted in the NHSME CRC Needs Assessment Review (2), and corresponds most closely with the levels of 54% and 58% reported in 1990 and 1992 for non-rehydrated guaiac tests in preliminary results from the Nottingham trial (21,22). Rehydration of guaiac FOBT slides only yields greater sensitivity at the price of lower specificity, ie higher false-positivity rates.…”
Section: Sensitivity Of Fortsupporting
confidence: 82%
“…A total of 421 full papers were retrieved, of which 38 were finally considered relevant for the review 1112 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 Reference checking yielded 11 additional relevant papers 863 64 65 66 67 68 69 70 71 72 As four papers8 29 30 72 presented information on two studies, our total number of primary diagnostic studies for inclusion was 47.…”
Section: Resultsmentioning
confidence: 99%
“…66 67 68 Of the 33 studies in secondary care, 20 were performed in diagnostic clinics (colonoscopy,8 27 32 36 37 39 41 43 45 46 50 51 52 53 55 71 double contrast barium enema54 57 62 64) and 13 in outpatient clinics 1112 29 35 38 42 47 48 56 58 59 60 69 Prevalence of colorectal cancer ranged from 0.4% to 15%.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Coloscreen Self-Test was also less sensitive. 16 Immunological tests also exist. One, Hemeselect, was compared with Haemoccult, in a population with gastrointestinal symptoms on three consecutive daily bowel motions.…”
Section: N Intestinal Obstructionmentioning
confidence: 99%